Strategy for Implementing the Bible Integration Curriculum on Thematic Subjects in Virtual Learning in XYZ Dan Mogot School - Endang Meryah Simbolon; Khoe Yao Tung (Jurnal Pendidikan Tambusai, 2022)
XYZ Daan Mogot Kindergarten was a Christian school that implemented Bible integration in its learning activities. Even though XYZ Kindergarten school already had an integrated Bible curriculum, teachers had difficulties and confusion in implementing it. This study aimed to describe how Bible integration was incorporated into the curriculum on thematic subjects in virtual learning at XYZ Kindergarten, explained how the level of application of Bible integration was and explained the obstacles experienced by schools. The method that will be carried out by the researcher was qualitative research using research instruments such as interviews, questionnaires, class observations, and documents. The results of the research show that: Bible integration in XYZ Kindergarten is the realization of the great mandate where its implementation is contained in the curriculum, teacher’s examples, and also the recruitment of new employees. The level of application of Bible integration in XYZ Kindergarten has not yet reached a complete stage. The obstacles faced by schools include the personal faith of the teacher, the ability of the teacher, limited time, lack of resources and problems from parents.